2018
DOI: 10.1149/08607.0207ecst
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Growth of Si-Ge-Sn Pseudomorphic Layers on 200 mm Ge Virtual Substrates: Impact of Growth Pressure, HCl and Si2H6 Flows

Abstract: We have quantified the impact of various process parameters on the growth of thin, pseudomorphic SiyGe1-x-ySnx layers on 2.5 µm Ge buffers (themselves on Si(001) substrates). For GeSn layers, we found that 100 Torr was appropriate for the growth of high crystalline quality layers. The impact of the HCl mass-flow on the growth kinetics of thin Ge1-xSnx layers was also evaluated. Adding HCl retained Ge in the gaseous phase, resulting at 325°C in a growth rate decrease and a Sn content increase. Moreover, the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 23 publications
7
19
0
Order By: Relevance
“…1(d): The optically active GeSn 16.0% layer was 418 nm thick. Based on a recent study on the growth kinetics of SiGeSn thin layers at 349°C [22], we would expect the Si and Sn contents in the bottom SiGeSn layer to be close to 9% and 8%, respectively. Strain relaxation that occurred during the growth of the step-graded structure might have had an impact on the composition of the top SiGeSn layer (which was deposited with exactly the same parameters of the bottom one).…”
Section: Epitaxy and Fabrication Methodsmentioning
confidence: 99%
“…1(d): The optically active GeSn 16.0% layer was 418 nm thick. Based on a recent study on the growth kinetics of SiGeSn thin layers at 349°C [22], we would expect the Si and Sn contents in the bottom SiGeSn layer to be close to 9% and 8%, respectively. Strain relaxation that occurred during the growth of the step-graded structure might have had an impact on the composition of the top SiGeSn layer (which was deposited with exactly the same parameters of the bottom one).…”
Section: Epitaxy and Fabrication Methodsmentioning
confidence: 99%
“…Germanium thin films find applications in waveguides in integrated photonic circuits [4,5]. Ge thin films also act as buffers for the growth of group IV alloys such as GeSn and SiGeSn on Si substrates to counter the issue of the large lattice mismatch between the alloys and Si substrate [6]. These group IV alloys can then be bandgap and lattice engineered by varying their atomic compositions to achieve active photonic components such as light emitting diodes, lasers, and detectors [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the limited thermal budget, the growth of SiGeSn faces some additional challenges. Khazaka et al previously reported rough surfaces with a grainy〈110〉 cross-hatch 27 and maximum Si contents of 17%, 28 while the crystalline quality of the film was good. Concerning electrical activation, it was found, in a GeSn(:B/:P) in situ doping study, 23 that B atoms in substitutional sites were almost fully electrically active.…”
mentioning
confidence: 95%